Keterlambatan Laporan Akuisisi Saham PT. Citra Asri Property Oleh PT. Plaza Indonesia Realty Tbk Menurut Undang-Undang Nomor 5 Tahun 1999 - Muhammad Yasser Kahfie; Euis Amalia (JOURNAL of LEGAL RESEARCH, 2019)
Abstract.The Business Competition Supervisory Commission is an independent state institution that functions as a supervisor, fact-seeker as well as a decision maker regarding violations of the law in the field of business competition. After considering several KPPU decisions related to the delay in the share acquisition report, a discrepancy was found between the sound legal considerations of KPPU Decision Number 02 / KPPU-M / 2017 with Article 29 of Law Number 5 of 1999 and Article 6 of Government Regulation Number 57 of 2010, where The Commission Council only included Article 47 of Law Number 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition in which explaining administrative sanctions in the form of fines of as low as one billion rupiahs and as high as twenty-five billion rupiahs and not yet explained in full the articles contained in the implementing regulations regarding the imposition of financial penalties for each day of delay. The imposition of administrative sanctions in the KPPU Decision Number 02 / KPPU-M / 2017 does not comply with the provisions of Article 29 of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition and Article 6 of Government Regulation Number 57 of 1999 Concerning Merger or Consolidation Business Entities and Corporate Share Acquisitions That Can Result in Monopolistic Practices and Unfair Business Competition.Keywords: Business Actors, Stock Acquisition Report, KPPU, Business Competition